Quality by Design Enabled Development and Optimization of the Nanoparticulate System of Cabazitaxel (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Cabazitaxel (CTX), a novel taxane derivative, has proven effective in many solid tumors. It is also approved in many countries for multiple uses in solid tumors. The current marketed formulation lacks the tumor-targeting ability, and its uneven distribution in the body causes toxicity to normal tissues. Further, it is a surfactant (polysorbate 80) based micellar formulation composed of ethanol as a co-solvent to improve the solubility of CTX, which causes severe and life-threatening side effects. Hence, to avoid the problem associated with this conventional CTX formulation, the nanoparticulate drug delivery system of CTX was developed by employing the Quality by Design (QbD) approach. The CTX nanoparticulate system was developed by employing a bottom-up followed by a top-down approach. The size reduction was obtained by High-Pressure Homogenizer (HPH). The formulation optimization was done using QbD approach. Design of experiments (DoE) was used to understand the effect of various formulation and process variables on a dependent variable like particle size distribution.The stabilizer concentration, concentration of solubilizer, HPH pressure, and passes were selected as independent factors while particle size distribution was selected as a dependent factor for evaluation. The nanoparticulate system was developed using PEG-400 as solubilizing agents, while Soya Phosphatidylcholine (SPC) was used as a surface stabilizer. Response surface plots revealed a decrease in particle size with increasing concentration of SPC and PEG 400. Similarly, a decrease in particle size with increased HPH passes and pressure was found. The optimum concentrations of SPC and PEG 400 were found to be 20% and 2.5%, respectively. 20 KPSI pressure and 5 HPH passes were derived as optimized processing parameters from DoE. The optimized formulation had a size of 43.5 nm, with PDI < 0.4. Due to its narrow particle size distribution, the formulation did not show any increase in particle size or aggregation up to 24 hours. The present research confirms the feasibility of developing the nanoparticulate system of CTX using the bottom-up followed by the top-down technique. The formulation was systematically optimized using QbD approach. The optimum concentration of PEG 400 as solubilizer and concentration of SPC as stabilizer was obtained from DoE, yielding optimum particle size and stability.